Analisis Implementasi dan Evaluasi Fitur SIMKO Mobile KSPPS BMT Lima Satu Jepara Melalui Pendekatan Model UTAUT - Benzi, Kifa Yola; Mubarok, Ahmad Fauzan; Utami, Cahyaning Budi (LABATILA : Jurnal Ilmu Ekonomi Islam, 2025)
This study aims to evaluate the implementation of the SIMKO Mobile feature at KSPPS BMT Lima Satu Jepara using the UTAUT model approach. SIMKO Mobile is a digital application developed to make it easier for cooperative members to access financial services such as checking balances, transaction history, and saving and borrowing independently. The results of the study indicate that the implementation of this application can improve service efficiency and provide flexibility for officers and members. However, there are several inhibiting factors that are divided into two categories, namely internal and external. Internal factors include lack of socialization, unavailability of adequate guidance, and application features that do not fully meet the needs of members. While external factors include limited devices, unstable internet connections, and member preferences for alternative services such as WhatsApp Mobile. Evaluation using the UTAUT model shows that although performance expectations and ease of use are quite good, social factors and supporting facilities are still not optimal. For this reason, it is necessary to strengthen the promotion strategy, develop features that are more in accordance with user needs, and increase digital education for members so that the implementation of SIMKO Mobile can run more optimally and have a significant impact on the cooperative.